Administrative Efficiency in Elderly Welfare Provision of the Waeng Subdistrict Administrative Organization, Narathiwat Province, Thailand - แวหะมะ, ชารีฟ; เจ๊ะเม๊าะ, นูรฟะฮ์มีย์; โต๊ะดง, ชารีฟ; สุขเสนีย์, คมวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aims to: (1) examine the model of elderly social welfare provision of the Waeng Subdistrict Administrative Organization, Waeng District, Narathiwat Province; and (2) propose guidelines for improving the efficiency of elderly welfare management. A qualitative approach was employed, with five key informants purposively selected, including an administrator, a social welfare officer, and three elderly individuals. Data were collected through in-depth interviews using a semi-structured guide and analyzed by content analysis. The findings indicate that elderly welfare provision comprises four main components: social services, social insurance, proactive social assistance through multi-sectoral collaboration, and social partnership support. However, limitations were found in terms of budget constraints, insufficient personnel, and a lack of continuous inter-agency integration. To enhance efficiency, development should address four dimensions: physical (proactive healthcare), environmental (safe and accessible environments), psychological (capacity building and reduced isolation), and social relationships (strengthening participation of families and communities). In addition, greater emphasis should be placed on inter-agency collaboration, capacity building for personnel and volunteers, and effective dissemination of welfare information. These measures aim to sustainably improve the quality of life and self-reliance of older persons.